Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/jamia/ocab053
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physician burnout with organizational electronic health record support and after-hours charting

Abstract: In 2017, 43.9% of US physicians reported symptoms of burnout. Poor electronic health record (EHR) usability and time-consuming data entry contribute to burnout. However, less is known about how modifiable dimensions of EHR use relate to burnout and how these associations vary by medical specialty. Using the KLAS Arch Collaborative’s large-scale nationwide physician (MD/DO) data, we used ordinal logistic regression to analyze associations between self-reported burnout and after-hours charting and organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…Physician stress and burnout, particularly associated with technology use, were issues of considerable interest prepandemic. 3 4 5 6 7 In the context of a public health crisis that placed extraordinary responsibilities on health care professionals and contributed to deterioration of work–life happiness, clinician well-being has become an even greater concern. 8 9 As telehealth adoption and availability grows, so does the need to understand providers' perceptions of its benefits, burdens, and barriers.…”
Section: Background and Significancementioning
confidence: 99%
“…Physician stress and burnout, particularly associated with technology use, were issues of considerable interest prepandemic. 3 4 5 6 7 In the context of a public health crisis that placed extraordinary responsibilities on health care professionals and contributed to deterioration of work–life happiness, clinician well-being has become an even greater concern. 8 9 As telehealth adoption and availability grows, so does the need to understand providers' perceptions of its benefits, burdens, and barriers.…”
Section: Background and Significancementioning
confidence: 99%
“…When selecting which metrics to use to assess for physician burden, we used metrics that evaluate time spent in the EHR outside working hours. Studies have demonstrated associations between both self-reported [14][15][16] and objective 17 measures of time spent in the EHR with physician burnout as measured by validated surveys such as the Maslach Burnout Inventory survey and the AMA mini-Z measurement. We evaluated burden using the metrics: Descriptive statistics were generated for all eleven metrics across the three time periods among all physicians, by specialty group, and by gender.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 58 More recently, data from the KLAS Arch Collaborative found that physicians who reported their organization had done a “great job with EHR implementation, training, and support” were twice as likely to report lower burnout scores. 59 Children's Hospital of Philadelphia created a more customized one-on-one training and efficiency program for their physicians and were able to reduce burnout rates from 32% to 23%. 60 …”
Section: Organizational Interventionsmentioning
confidence: 99%